The Rank-Size Rule in Europe - testing Zipf's law using European data - Graham Crampton (European Regional Science Association (ERSA), 2005)
The large literature on the rank-size rule of city sizes has received rather inconsistent treatment in the European continent. Part of the problem has been the fact that (unlike the U.S.) there are inconsistent Census dates and no uniform definition of what is meant by an urban area. This paper uses data from a French research project which provides physical urban area data for a number of (not all) European countries, down to quite small minimum urban sizes. This allows international comparison of the usual Pareto estimation parameters, and also some examination of whether square or cubic terms are significant. The nature and economic basis of such non-linearities in the logarithmic rank-size relationship are of interest. The spatial nature of the urban size hierarchy has also been rather neglected recently, and much research in this area has virtually ignored the location of the cities, focusing solely on size. Appropriate treatment of nearby urban centres is a tricky empirical problem, as is the proper treatment of urban areas spreading across two or more countries. One of the main background economic motives for studying urban size hierarchies in Europe is to speculate on whether the development of the Eurozone may lead to movement towards a U.S.- type size distribution, which follows the rank-size rule rather well.
Keywords: 330